[A.I.D.S. ; Baguio Baby ; Solar energy [videorecording] (The Probe Team, 1992)
An interview with persons with AIDS. Takes a look into the second reported case of a newborn baby being kidnapped in Baguio General Hospital and into the program to supply solar energy panels at low costs by the National Electrification Administration.